Students’ metacognition as a mediator between instruction and student cognition / Ng Peng Lan - Ng, Peng Lan (2012)
This qualitative case study complemented by quantitative data analysis examined pre-university Sociology students‘ metacognitive processes and how their strategies change based on achievement and metacognition levels. The Planned Action Interview (PAI) on 53 students‘ metacognitive processes found three phases: Metacognitive Knowledge (MK), Metamotivators(MM), and Metacognitive Regulation (MR) and three dimensions of learning: metacognitive, cognitive, and behavioral. First, at the metacognitive dimension, MM mediates between MK and MR. Second, at the cognitive dimension, student metacognition mediates between instruction and learning. Student metacognition improves through reflecting, monitoring, controlling, and motivating strategies. The metacognitive profile of eight high achievers consisted of an evaluative reflectivist, high self-knowledge, self-motivated, high self-control, and self-constructivist. This profile provided guidelines to facilitate use of metacognitive skills. Characteristics of effective meta-tasks found were reflectivist, self-constructivists, engaging, evaluative, and optimally challenging tasks. The Planned Action Scale (PAS) consisting of 85 items was administered to 115 pre-university students. Both the PAI and PAS were adapted from the Motivated Strategies for Learning Questionnaire (MSLQ: Pintrich et.al 1991) and the Metacognitive Awareness Inventory (MAI: Schraw& Dennison, 1994). A one-way ANOVA compared the mean achievement scores of 115 students that were grouped as low, medium, and high metacognition. A significant difference was found, F (2, 112) = 8.50, p=0.001. Further analysis using a hierarchical regression technique showed that instructional task and student metacognition have a significant standardized effect, F (2, 112) = 18.52, p < .001 on student achievement scores. The qualitative and quantitative findings support the mediating role of metacognition in The Theory of Metacognitive Action Learning Strategies (MALS) for effective learning outcomes and future instructional designs.